Organization and function of Drosophila odorant binding proteins. - Larter, N.K.; Sun, J.S.; Carlson, J.R. (eLife, 2016)
Odorant binding proteins (Obps) are remarkable in their number, diversity, and abundance, yet their role in olfactory coding remains unclear. They are widely believed to be required for transporting hydrophobic odorants through an aqueous lymph to odorant receptors. We construct a map of the Drosophila antenna, in which the abundant Obps are mapped to olfactory sensilla with defined functions. The results lay a foundation for an incisive analysis of Obp function. The map identifies a sensillum type that contains a single abundant Obp, Obp28a. Surprisingly, deletion of the sole abundant Obp in these sensilla does not reduce the magnitude of their olfactory responses. The results suggest that this Obp is not required for odorant transport and that this sensillum does not require an abundant Obp. The results further suggest a novel role for this Obp in buffering changes in the odor environment, perhaps providing a molecular form of gain control.